Tourist Attraction, Accessibility, and E-WOM Roles on Visit Decisions to Cacalan Beach: Visiting Interest Mediation - Halim, Naufal; Abidin, Zainal (Grouper, 2025)
Tourism is a strategic sector that plays a significant role in driving economic growth and improving community welfare. Banyuwangi Regency possesses substantial coastal tourism potential, one of which is Cacalan Beach. Despite offering appealing natural attractions, good accessibility, and active digital promotion through electronic word of mouth (e-WOM), the abundance of similar beach destinations presents a challenge for Cacalan Beach in maintaining its competitiveness as a top choice for tourists. This study aims to analyze the influence of tourist attraction, accessibility, and e-WOM on tourists' visit decisions, with visiting interest as a mediating variable. The research employed a quantitative descriptive approach, involving 140 respondents who met the criteria, using a questionnaire as the data collection tool. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with WarpPLS version 8.0. The results indicate that tourist attraction has a direct influence on visit decisions, while accessibility and e-WOM do not show a direct effect. However, all three variables significantly enhance visiting interest, which in turn contributes to an increase in actual visits to Cacalan Beach. These findings highlight that visiting interest plays a crucial role in encouraging tourists' decisions to visit.